ERC Decision of 29 November 1999 on Exemption from Individual Licensing of Receive Only Earth Stations (ROES) (CEPT/ERC/DEC/(99)26) - Stéphan le Goueff (Satellite Regulation in Europe, 2000)
Effective treatment of metastatic neuroendocrine tumors (NETs) is limited by a lack of targeted therapies and clinically useful predictive biomarkers. We applied complementary genomic profiling technologies, including optical genome mapping (OGM) and whole exome sequencing (WES), to 70 liver metastases of NETs from multiple anatomical primary sites to identify actionable genomic alterations. We detected recurrent fusions involving TBL1X (PSIP1::TBL1X) and BEND2 (CHD7::BEND2 and NEO1::BEND2) by OGM in pancreatic neuroendocrine tumors (pNETs). The expression of the PSIP1::TBL1X fusion was confirmed by PacBio Iso-Seq long-read transcriptome sequencing and nested rtPCR, and fusion protein expression was established by western blotting. Expression of the PSIP1::TBL1X fusion was also assayed in a separate cohort of 31 specimens from 28 pNET cases by rtPCR. Across both cohorts, PSIP1::TBL1X was identified in 11% of pNET patients with available metastatic tissue, but was not detected in primary tumor specimens. All PSIP1::TBL1X fusion isoforms were found to retain early exons of PSIP1 and the complete coding sequence of TBL1X. Consistent with prior reports, BEND2 fusions were associated with high-grade tumors and may represent a clinically useful biomarker for aggressive disease. Notably, TBL1X and BEND2 fusions are mutually exclusive with ATRX/DAXX mutations, defining a distinct molecular subgroup of pNETs. This study highlights the importance of structural variant profiling in molecular profiling studies and supports a revised view of the role of gene fusions in neuroendocrine malignancies.